Pedagogia a lápis cor de pele: educação das relações étnico-raciais em cursos de pedagogia de universidades públicas localizadas no estado de São Paulo - Silva, Mariana Martha de Cerqueira (2021)
This research analyzed, in Pedagogical Projects of Pedagogy Courses (PPCs), how proposals to combat racism are revealed (or not), according to definitions present in the National Curriculum Guidelines for Education of Ethnic-Racial Relations and for the Teaching of Afro-History and Culture. Brazilian and African (DCNERER). It starts from the initial consideration that the DCNERER propose intentional pedagogical actions to combat racism, including in pedagogy courses, the central locus of the academic path of education professionals. Scientific studies on racial issues and the curricula of pedagogy courses indicate that there is weak institutional support for the ERER approach in the curricula of these courses, as well as revealing that public universities located in the state of São Paulo occupy a prominent place in the investigations academics on this topic. From these findings came the elaboration of the question that guided this research: what do the pedagogical projects of the pedagogy course of public universities located in the state of São Paulo reveal (or not) about the ERER and how do they outline their proposals to combat racism? The corpus of this research consisted of 12 PPCs of Pedagogy from five public universities located in the state of São Paulo (USP, UNICAMP, UNESP, UFSCar and UNIFESP) and four guidelines: the DCNERER; the DCN Pedagogia, licenciatura; the DCN para formação inicial e continuada and the DCN BNC-Formação, which are curricular policies that guide these courses. Anti-racist investigation and document analysis were the paths selected to categorize the discursive references relating to the education of ethnic-racial relations present in national curriculum guidelines and, consequently, in the analyzed PPCs. The results indicated that the approaches to the ERER, present in these sets of documents, were presented more to confirm the existence of the racial issue than to deepen the debate on this subject as a pedagogical problem. Such racial approaches did not constitute political insertions that recognized the meanings of racial inequities present in our society, nor in explicit proposals to combat racism, as prescribed by the DCNERER. The final considerations indicate that, in the universe of researched pedagogy courses, the discourse of confronting racism is marked by intentional political omissions. It is possible that this is due to the negligence of these courses in referring and promoting educational actions that meet the ERER principles and regulatory frameworks. In addition to these findings, new problematizations generated from the research results are indicated in the considerations.